# Algebra II

1)What method(s) would you choose to solve the equation:

x2 + 2x - 6 = 0

A. Square roots; there is no x-term.

B. Quadratic formula, graphing; the equation cannot be factored easily since the numbers are large.

C. Factoring; the equation is easily factored.

D. Quadratic formula, completing the square or graphing; the coefficient of x2-term is 1, but the equation cannot be factored. <<<------

2)What are the solutions of the equation?
c^2 - 10c = 0

A. 1, – squareroot10 <<<----

B. 0, –10

C. 0, sqrt10

D. 0, 10

3)Use the discriminant to determine the number of real-number solutions for the equation:
8x2 + 8x + 2 = 0

A. one solution <<<---

B. two solutions

C. no solutions

D. infinitely many solutions

4)What are the solutions of the equation: z2 - 12z + 36 = 0?

A. -6, 6 <<----

B. 6, 6

C. 6, -6

D. -6, -6

thank u!

1. 👍 0
2. 👎 0
3. 👁 482
1. 1. I would choose B.

2. c^2 - 10c = c(c-10) = 0
Now what do you think?

4. z^2 - 12z + 36 = (z-6)(z-6) = 0
Now what do you think?

3. Since it seems like you are just guessing, I did not bother to answer.

1. 👍 0
2. 👎 1

## Similar Questions

1. ### algebra 2

If you were to use the substitution method to solve the following system, choose the new equation after the expression equivalent to x from the first equation is substituted into the second equation. x + y = 2 3x + 2y = 9

asked by mel on August 16, 2012
2. ### Algebra 2

If you were to use the substitution method to solve the following system, choose the new equation after the expression equivalent to x from the first equation is substituted into the second equation. x – 2y = 2 x + 3y = 17

asked by Mike on April 25, 2011
3. ### How do I do this.?(Math.)

Use the Substitution method to solve the system of equations. y - 2x = -5 3y - x = 5 Solve one of the equations for x or y. Let's solve the first one for y: y - 2x = -5 y = 2x - 5 Now let's substitute 2x - 5 for y in the second

asked by Margie on February 5, 2007
4. ### Substitution Method-Plz help

Use the Substitution method to solve the system of equations. x + y = -4 x - y = 2 solve for x in the second equation. x= y+2 Put that in for x in the first equation: x+y=-4 (y+2) + y = -4 solve for y. Then, x= y+2 i don't get

asked by Svetlana on October 17, 2006
5. ### ALGEBRA 1!PLZ HELP!

Use the Substitution method to solve the system of equations. y - 2x = -5 3y - x = 5 Solve the first equation for y. y = 2x-5 Substitute that for y in the second equation and solve for x. Then use the value of x to substitute back

asked by SANDRO! on November 6, 2006
1. ### math,algebra II

I need someone to explain to me step by step the process of this problem its in my book as an example but i am not understanding it. Ive researched the explanation of the ECHELON METHOD...BUt i am not seeingit...this is the

asked by alma20 on June 1, 2007
2. ### math

What is the first step in solving the linear system {2x − 3y = 11 {−x + 5y = −9 by the substitution method in the most efficient way? A. Solve the first equation for x. B. Solve the first equation for y. C. Solve the second

asked by math on March 31, 2020
3. ### math

What is the first step in solving the linear system {2x−3y=11 {−x+5y=−9 by the substitution method in the most efficient way? A. Solve the first equation for x. B. Solve the first equation for y. C. Solve the second equation

asked by CWOSSANT on April 3, 2020
4. ### Math

PLEASE CHACK MY ANSWER!!! Discussion for Applications of Linear Systems When solving a system of equations, how do you determine which method to use? My answer: I determine which method to use by looking at the equations. If both

asked by Matthew on December 15, 2016
5. ### Factoring

What does 3x^3-3x+2=0 come out to? How would I solve this? Is the x cubed supposed to be x squared? You can compare the equation with the identity: (a+b)^3 = a^3 + 3 a^2 b + 3 a b^2 + b^3 which you can rewrite as: (a + b)^3 = 3 ab

asked by Ace on May 30, 2007
6. ### maths

1.solve the set of linear equation by matrix method.a+3b+2c=3,2a-b-3c=-8,5a+2b+c=9 solve for a,b,c 2.solve by Guassian elimination method, (a)a+2b+3c=5,3a-b+2c=8,4a-6b-4c=-2, (b)

asked by emmanuel konwei on March 3, 2015

More Similar Questions